2013
DOI: 10.1155/2013/152073
|View full text |Cite
|
Sign up to set email alerts
|

The Parietal Cortex in Sensemaking: The Dissociation of Multiple Types of Spatial Information

Abstract: According to the data-frame theory, sensemaking is a macrocognitive process in which people try to make sense of or explain their observations by processing a number of explanatory structures called frames until the observations and frames become congruent. During the sensemaking process, the parietal cortex has been implicated in various cognitive tasks for the functions related to spatial and temporal information processing, mathematical thinking, and spatial attention. In particular, the parietal cortex pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…For instance, it has been suggested that the FEF region plays a crucial role in the construction of intrinsic reference frames among multiple objects in spatial tasks ( Wallentin, 2012 ). Likewise, studies with neural network simulations have shown that, although partial dissociation between different types of spatial information can occur by re-encoding visual information in the parietal cortex, dorsal control from the prefrontal cortex is necessary to achieve a more explicit dissociation ( Sun and Wang, 2013 ); Moreover, efficient and flexible representations of the changing environment requires the maintenance of both latent representations (through altered firing thresholds in non-frontal regions) and active representations (through sustained firing in the prefrontal cortex) ( Morton and Munakata, 2002 ). It is suggested that such a maintenance mechanism is involved when the infants created actor-object-location associations in the false-belief task ( Perner and Ruffman, 2005 ).…”
Section: From Spatial To Social: the Common Non-cognitive Originsmentioning
confidence: 99%
“…For instance, it has been suggested that the FEF region plays a crucial role in the construction of intrinsic reference frames among multiple objects in spatial tasks ( Wallentin, 2012 ). Likewise, studies with neural network simulations have shown that, although partial dissociation between different types of spatial information can occur by re-encoding visual information in the parietal cortex, dorsal control from the prefrontal cortex is necessary to achieve a more explicit dissociation ( Sun and Wang, 2013 ); Moreover, efficient and flexible representations of the changing environment requires the maintenance of both latent representations (through altered firing thresholds in non-frontal regions) and active representations (through sustained firing in the prefrontal cortex) ( Morton and Munakata, 2002 ). It is suggested that such a maintenance mechanism is involved when the infants created actor-object-location associations in the false-belief task ( Perner and Ruffman, 2005 ).…”
Section: From Spatial To Social: the Common Non-cognitive Originsmentioning
confidence: 99%